Science-based laboratory comprehension: an examination of effective practices within traditional, online and blended learning environments. (1st September 2016) - Rivera, Jennifer Hall
Abstract: An increase in online education is causing science educators to evaluate student cognitive understanding after completing virtual, computer-simulated laboratories. Online education has demonstrated comparable learning gains when analysed to those of the traditional classroom, but research is mixed when reviewing students' ability to manipulate tangible laboratory equipment after participating in online experimentation. The question remains, are students who are exclusively enrolled in online science courses equipped with the cognitive ability to operate laboratory equipment within a physical laboratory? When considering the optimal learning environment for science majors, educators have discovered the blended classroom may provide the perfect opportunity to combine the benefits of face-to-face instruction and feedback with the reinforcement of scientific theory through technology integration. New advances in virtual education provide promising examples of enhancing the online classroom laboratory in all scientific disciplines. Further insight into the blended classroom has the potential to influence the field of education towards an optimal learning environment for science majors in colleges and universities.